A surface metal ion-modified 3D-printed Ti-6Al-4V implant with direct and immunoregulatory antibacterial and osteogenic activity - Wu, Yipeng; Shi, Xiangwen; Wang, Jianjun; Li, Yang; Wu, Jiang; Jia, Daqi; Bai, Yan; Wu, Xiaopei; Xu, Yongqing (Frontiers in Bioengineering and Biotechnology, 2023)
The high concentration of antibacterial metal ions may exhibit unavoidable toxicity to cells and normal tissues. The application of antibacterial metal ions to activate the immune response and induce macrophages to attack and phagocytose bacteria is a new antimicrobial strategy. Herein, 3D-printed Ti-6Al-4V implants modified by copper, and strontium ions combined with natural polymers were designed to treat implant-related infections and osseointegration disorders. The polymer-modified scaffolds rapidly released a large amount of copper and strontium ions. During the release process, copper ions were employed to promote the polarization of M1 macrophages, thus inducing a proinflammatory immune response to inhibit infection and achieve the immune antibacterial activity. Meanwhile, copper and strontium ions promoted the secretion of bone-promoting factors by macrophages, induced osteogenesis and showed immunomodulatory osteogenesis. This study proposed immunomodulatory strategies based on the immunological characteristics of target diseases and provided ideas for the design and synthesis of new immunoregulatory biomaterials.